1999
DOI: 10.1074/jbc.274.50.35381
|View full text |Cite
|
Sign up to set email alerts
|

The MEK Pathway Is Required for Stimulation of p21WAF1/CIP1 by Transforming Growth Factor-β

Abstract: Transforming growth factor-␤ (TGF-␤)can induce the cyclin-dependent kinase inhibitors p21 and p15 in a variety of cell types. We have shown previously that Smad3 is required for the growth inhibitory activity of TGF-␤, whereas overexpression of Smads is not sufficient to activate the expression of p21 in HaCaT cells. These data suggest that an additional signaling pathway may be involved in stimulating p21 in HaCaT cells. Given the recent finding that the mitogen-activated protein kinase (MAPK) pathway can cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
1
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 41 publications
5
90
1
3
Order By: Relevance
“…This response was blocked in 3DdnS transfectants (Figure 3a), while no di erences for TGF-b 1 up-regulation of p21 Cip1 were observed between control PC and dominant-negative PdnS transfectants (Figure 3b,c). Since the Erk MAP kinase signalling pathway has also been implicated in the regulation of p21 Cip1 by TGF-b in epithelial cells (Yue et al, 1998;Hu et al, 1999), we studied the e ects of PD098059, a speci®c inhibitor of MAP kinase kinase (MEK) (Simon et al, 1996), on p21 Cip1 protein induction by TGF-b 1 . PD098059, at a concentration of 50 mM (that is shown to inhibit e ciently Erk signalling activity in PDV cells, see Smad4 and Ras co-operate for tumour progression M lglesias et al below), consistently reduced (by 35 ± 50%) TGF-b 1 -stimulated p21 Cip1 expression in PC and PdnS clones, while it did not a ect the enhancement of p21 Cip1 by the growth factor in 3DC cells ( Figure 3c).…”
Section: Smad4 Mediates Growth Inhibition In Both Mca3d and Pdv Keratmentioning
confidence: 99%
See 2 more Smart Citations
“…This response was blocked in 3DdnS transfectants (Figure 3a), while no di erences for TGF-b 1 up-regulation of p21 Cip1 were observed between control PC and dominant-negative PdnS transfectants (Figure 3b,c). Since the Erk MAP kinase signalling pathway has also been implicated in the regulation of p21 Cip1 by TGF-b in epithelial cells (Yue et al, 1998;Hu et al, 1999), we studied the e ects of PD098059, a speci®c inhibitor of MAP kinase kinase (MEK) (Simon et al, 1996), on p21 Cip1 protein induction by TGF-b 1 . PD098059, at a concentration of 50 mM (that is shown to inhibit e ciently Erk signalling activity in PDV cells, see Smad4 and Ras co-operate for tumour progression M lglesias et al below), consistently reduced (by 35 ± 50%) TGF-b 1 -stimulated p21 Cip1 expression in PC and PdnS clones, while it did not a ect the enhancement of p21 Cip1 by the growth factor in 3DC cells ( Figure 3c).…”
Section: Smad4 Mediates Growth Inhibition In Both Mca3d and Pdv Keratmentioning
confidence: 99%
“…The signalling pathways involved in these TGF-binduced gene responses remain an open question (see Massague , 1998). Thus, p21 Cip1 appears to be a downstream target gene regulated by Smad4 in carcinoma cells (Grau et al, 1997;Hunt et al, 1998), while it has been reported that Ras and the MAP kinase pathway are required for up-regulation of p21 Cip1 by TGF-b in intestinal epithelial cells and human keratinocytes, respectively (Yue et al, 1998;Hu et al, 1999). The same appears to occur for TGF-bmediated induction of other genes, such as the 3TP-lux reporter construct, which contains a known TGF-binducible plasminogen activator inhibitor-1 (PAI-1) promoter (Grau et al, 1997;Mucsi et al, 1996;de Winter et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in our understanding of the mechanisms by which the Smad and Ras/Mapk cascades mediate some TGF␤ effects, these pathways seem to regulate primarily transcriptional events (Hocevar et al, 1999;Hu et al, 1999;Sporn and Vilcek, 2000; Mulder, 2000a, 2001). However, TGF␤ is multifunctional and its biological responses are diverse.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the Ras/Mapk and Smad pathways, several proteins have been identified based upon their interaction with the TGF␤ receptors (Yue and Mulder, 2001). Furthermore, various Smad-interacting proteins have also been identified, including SARA and Dab2, which interact with both Smads and the TGF␤ receptors (Tsukazaki et al, 1998;Hocevar et al, 2001;Yue and Mulder, 2001).Despite advances in our understanding of the mechanisms by which the Smad and Ras/Mapk cascades mediate some TGF␤ effects, these pathways seem to regulate primarily transcriptional events (Hocevar et al, 1999;Hu et al, 1999;Sporn and Vilcek, 2000; Mulder, 2000a, 2001). However, TGF␤ is multifunctional and its biological responses are diverse.…”
mentioning
confidence: 99%